Urokinase-Type Plasminogen Activator Receptor (uPAR) in Inflammation and Disease: A Unique Inflammatory Pathway Activator - Mostafa Hamada; Kyle Steven Varkoly; Omer Riyadh; Roxana Beladi; Ganesh Munuswamy-Ramanujam; Alan Rawls; Jeanne Wilson-Rawls; Hao Chen; Grant McFadden; Alexandra R. Lucas (Biomedicines, 2024)
The urokinase-type plasminogen activator receptor (uPAR) is a unique protease binding receptor, now recognized as a key regulator of inflammation. Initially, uPA/uPAR was considered thrombolytic (clot-dissolving); however, recent studies have demonstrated its predominant immunomodulatory functions in inflammation and cancer. The uPA/uPAR complex has a multifaceted central role in both normal physiological and also pathological responses. uPAR is expressed as a glycophosphatidylinositol (GPI)-linked receptor interacting with vitronectin, integrins, G protein-coupled receptors, and growth factor receptors within a large lipid raft. Through protein-to-protein interactions, cell surface uPAR modulates intracellular signaling, altering cellular adhesion and migration. The uPA/uPAR also modifies extracellular activity, activating plasminogen to form plasmin, which breaks down fibrin, dissolving clots and activating matrix metalloproteinases that lyse connective tissue, allowing immune and cancer cell invasion and releasing growth factors. uPAR is now recognized as a biomarker for inflammatory diseases and cancer; uPAR and soluble uPAR fragments (suPAR) are increased in viral sepsis (COVID-19), inflammatory bowel disease, and metastasis. Here, we provide a comprehensive overview of the structure, function, and current studies examining uPAR and suPAR as diagnostic markers and therapeutic targets. Understanding uPAR is central to developing diagnostic markers and the ongoing development of antibody, small-molecule, nanogel, and virus-derived immune-modulating treatments that target uPAR.